Technical Solutions to the Problem of Contaminated Cabin Air - Dieter Scholz (Deutsche Gesellschaft für Luft- und Raumfahrt, 2018)
>>> Purpose – This presentation gives an introduction to the problem of contaminated cabin air and points out possible solutions especially by looking at carbon filters placed in the main path of the bleed air from the engine to the cabin ("total cabin air filtration") in additon to filters in the cabin air recirculation path. Maintenance issures related to the topic are also considered. >>> Design/methodology/approach – The literature review is complemented with own explanations, thoughts and derivations. >>> Findings – There is a real health and flight safety risk due to contaminated cabin air. For the infrequent flyer the risk is very low. Also aviation statistics are not dominated by cabin air related accidents. Nevertheless, a bleed air based air conditioning system can be regarded as applying a fundamentally wrong systems engineering approach. A substantial improvement of the situation can only be reached with filters added to the large fleet of existing airplanes. A full solution, however, requires airconditioning with outside air and dedicated compressors. >>> Research limitations/implications – The study is based primarily on references. >>> Practical implications – Passengers and crew are made aware of the risk of cabin air contamination based on technical facts. Given detailes of technical solutions contribute to the scientific discussion. >>> Social implications – Better knowledge of the problem should enable passengers and crew to maintain a firm position in the sometimes heated discussion. >>> Originality/value – Engineering based information with a critical view on the topic seems to be missing in public. This presentation contributes filling this gap.
Keywords: Luftfahrt; Luftfahrzeug; cabin; Kabinenluft; Kontamination; aviation; aircraft; air; contamination; fume event; smell event; CACE; filter; recirculation; bleed air; air conditioning; compressor